Pembinaan Keagamaan Siswa melalui Pelatihan Praktik Ibadah dan Lomba Islami di SMP Muhammadiyah 05 Medan - Marzuki Marzuki; Luthfiyah Az Zahra; Filza Syahira; Rizki Khairani; Abdul Qohar; Muhammad Irvan Prayandy; Harji Alfa Rabi (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
The internship activities of students from the Qur’anic Studies and Tafsir Department at Universitas Islam Negeri Sumatera Utara represent a form of community service aimed at providing tangible contributions in accordance with their field of expertise. Although the students do not come from an education major, the interns at SMP Muhammadiyah 05 Medan actively participated in the religious guidance of students. The guidance activities included mentoring in Qur’an learning, Islamic Religious Education (PAI), and tahfidz (Qur’an memorization), as well as training in practical acts of worship such as the procedures for ghusl janabah (ritual purification after major impurity) and the funeral prayer (salat al-janazah). In addition, the interns also organized various Islamic competitions, including short surah recitation contests, Islamic quiz competitions, and the call to prayer (adhan) competition. This study employed a descriptive method with a qualitative approach, where data were obtained through observation, documentation, and direct participation during the internship activities. The results indicate that religious guidance through practical worship training and Islamic competitions can enhance students’ understanding, skills, and enthusiasm in practicing Islamic teachings. Therefore, the student internship program provides a positive contribution in strengthening religious values and the religious character of students at SMP Muhammadiyah 05 Medan.